2022
DOI: 10.1097/mao.0000000000003658
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Endolymphatic Hydrops in Cochlear Implant Candidates with Idiopathic Profound Sensorineural Hearing Loss

Abstract: ObjectiveTo determine the prevalence of endolymphatic hydrops (EH) in cochlear implant (CI) candidates with idiopathic profound sensorineural hearing loss (SNHL) and its influence on the preservation of audiovestibular function after cochlear implantation.Study DesignProspective case series.SettingTertiary referral center.PatientsCI candidates with idiopathic progressive SNHL, but without classic EH-associated symptoms.InterventionsDelayed intravenous gadolinium-enhanced inner ear fluid-attenuated inversion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
(110 reference statements)
0
3
0
1
Order By: Relevance
“…SEH after CI (due to fibrosis and trauma) has been commonly reported in histological studies of human CI recipients, with prevalence rates ranging from 41 to 58% in line with our current findings (10,27). However, recent studies in implanted guinea pig cochlea reveal that EH is prevalent in the first weeks after surgery even in the absence of significant electrode trauma (28). Furthermore, a recent study by Mosimann et al (28) revealed that EH was found in 28% of CI candidates with idiopathic profound SNHL, but with no other EH-associated symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SEH after CI (due to fibrosis and trauma) has been commonly reported in histological studies of human CI recipients, with prevalence rates ranging from 41 to 58% in line with our current findings (10,27). However, recent studies in implanted guinea pig cochlea reveal that EH is prevalent in the first weeks after surgery even in the absence of significant electrode trauma (28). Furthermore, a recent study by Mosimann et al (28) revealed that EH was found in 28% of CI candidates with idiopathic profound SNHL, but with no other EH-associated symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies in implanted guinea pig cochlea reveal that EH is prevalent in the first weeks after surgery even in the absence of significant electrode trauma (28). Furthermore, a recent study by Mosimann et al (28) revealed that EH was found in 28% of CI candidates with idiopathic profound SNHL, but with no other EH-associated symptoms. In our group, the cause of hearing loss for these patients included adult-onset progressive hearing loss, congenital/childhood-onset hearing loss, SSNHL, and other causes.…”
Section: Post-ci Sehmentioning
confidence: 99%
See 1 more Smart Citation
“…Es wird deshalb eine Assoziation zum Auftreten eines endolymphatischen Hydrops nach der Implantation angenommen [18]. Die Inzidenz eines endolymphatischen Hydrops nach CI wird mit 59 % angegeben [19], während sie vor der Implantation bei nur etwa 28 % liegt [20].…”
Section: Klinikunclassified